2017
DOI: 10.4103/ijc.ijc_168_17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of first-line systemic chemotherapy with epirubicin, cisplatin plus 5-fluorouracil and docetaxel, cisplatin plus 5-fluorouracil regimens in locally advanced inoperable or metastatic gastric or gastroesophageal junction adenocarcinoma: A prospective phase II study from South India

Abstract: In comparison to ECF, the DCF regimen was associated with a statistically significant 3.1 months longer median OS without any significant increase in Grades 3-4 toxicities. DCF can be considered as one of the reference regimens, in properly selected patients with advanced/metastatic gastric or GEJ adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Moreover, our reported one and two-year OS, as well as ORR (75.5%) and DCR (89.1%), was comparable with other similar studies administrated FOLFOX7 and modified-FOLFOX6 regimens [12,30]. However, our 30% OS rate after three-year follow-up was in disagreement with the approximate amount of 60% which was reported in the previous studies [10,12,29,30]. The lower OS rate in patients who had received FOLFOX regimen in our study can be attributed to the higher median age of our enrolled patients (60 years old) in comparison with the other important studies with less than 50 years old patients recruitment [10,12].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, our reported one and two-year OS, as well as ORR (75.5%) and DCR (89.1%), was comparable with other similar studies administrated FOLFOX7 and modified-FOLFOX6 regimens [12,30]. However, our 30% OS rate after three-year follow-up was in disagreement with the approximate amount of 60% which was reported in the previous studies [10,12,29,30]. The lower OS rate in patients who had received FOLFOX regimen in our study can be attributed to the higher median age of our enrolled patients (60 years old) in comparison with the other important studies with less than 50 years old patients recruitment [10,12].…”
Section: Discussionsupporting
confidence: 73%
“…In the resemblance with recently published meta-analysis [27,28], our cox-regression analysis demonstrated that there was a significant difference between OS enhancement by ECF and DCF regimens. The superiority of taxane-based regimen over non-taxane-containing chemotherapy was confirmed by Chaudhuri et al not only inoperable gastric cancer patients but also in the metastatic situation [29]. Besides, we found that the PFS of patients receiving the DCF regimen was higher than the ECF regimen, despite non-statistically significant results.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…From our results, four studies[9,10,12,19] showed that DCF significantly prolonged the OS of patients compared with ECF, and three studies[8,9,19] showed that DCF significantly prolonged the PFS of patients compared with ECF. The results were beneficial to the translation of OS and PFS from the DCF regimen to the pooled median survival time of approximately 1 mo.…”
Section: Discussionmentioning
confidence: 63%
“…Recommended by clinical guidelines, docetaxel, cisplatin, and 5-fluorouracil (DCF) and epirubicin, cisplatin, and 5-fluorouracil (ECF) regimens are commonly used as first-line treatments for gastric cancer[7]. The results in some studies showed that the DCF group was better than the ECF group in terms of objective response rate (ORR), progression-free survival (PFS), and overall survival (OS)[8-9]. However, in other studies, opposite results were obtained, and the ECF regimen had better antitumor efficacy and better quality of life for advanced gastric cancer[10,11].…”
Section: Introductionmentioning
confidence: 99%